#### Answer

$-18$

#### Work Step by Step

$\sum ^{5}_{i=2}\left( 6-3i\right) =\sum ^{5}_{i=2}\dfrac {63}{}\sum ^{5}_{i=2}i=\sum ^{4}_{i=1}\dfrac {63}{}\sum ^{5}_{i=2}i=4\times 6-3\left( 2+3+4+5\right) =-18$

Published by
Pearson

ISBN 10:
013421742X

ISBN 13:
978-0-13421-742-0

$-18$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.